Cognitive Behavior Modification (CBM) Approach in Stress Management among Long-Term Inmates at Class IIA Correctional Facility Cikarang - Zain Difa Waliyudin; Iman Santoso (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2026)
Abstract Introduction to the Problem: Stress is a significant psychological challenge for long-term inmates caused by restricted freedom, separation from family, and the burden of lengthy sentences. These conditions often lead to negative thought patterns, maladaptive behaviors, and hinder the rehabilitation process. Purpose/Study Objectives: This study aims to analyze the implementation of Cognitive Behavior Modification (CBM) in managing stress among long-term inmates at the Class IIA Correctional Facility Cikarang. Design/Methodology/Approach: The research employs a descriptive qualitative approach through interviews, observations, and documentation to explore inmates’ experiences and psychological dynamics in participating in CBM-based rehabilitation programs. Findings: The results show that CBM is applied through religious, intellectual, and social development programs that help restructure negative cognitions, foster coping strategies, and strengthen resilience. However, several barriers remain, including low self-awareness, lack of motivation, negative stigma, limited psychological support, and inconsistent participation. These findings suggest that the success of CBM depends on inmates’ internal motivation, professional support, and the continuity of a rehabilitative environment. Paper Type: Research Article Keywords: Cognitive Behavior Modification; Stress Management; Long-Term Inmates; Correctional Facility; Rehabilitation